About competencies: What about creativity? - Victer Rosa (Rastros Rostros, 2023)
The formation of a citizen with the necessary skills to be able to face the universal reality requires a deep commitment on the part of the teacher in the creation of meaningful learning environments in which the acquired knowledge is used and the teacher demonstrates to himself that he is capable of performing in a concrete reality, facing the different structures with tenacity and decision.